Susceptibility of plum cultivar Roxa de Delfim Moreira to the internal breakdown after low-temperature storage - Evangelista, Regina Marta; Chitarra, Adimilson Bosco; Chitarra, Maria Isabel Fernandes (Pesquisa Agropecuaria Brasileira, 1992)
Plum fruit (Prunus salicina L.), cultivar Roxa de Delfim Moreira, at different stages of development, were stored for 20 days at 1±1oC temperature and 72-82% relative humidity, in order to evaluate their susceptibility to Internal Breakdown and texture characteristics. Plum fruits at a more advanced ripening stage which had a softer texture showed larger incidence of physiological injury.
Keywords: physiology; temperature; texture; fruits; maturation